The Right to Privacy under Fire – Foreign Surveillance under the NSA and the GCHQ and Its Compatibility with Art. 17 ICCPR and Art. 8 ECHR - Georgieva, Ilina (Utrecht Journal of International and European Law, 2015)
The recent exposure of the NSA documents has raised a great deal of concerns with regards to the effective control of companies that cooperate with intelligence agencies. It also exposed a network of secret government spying partnerships used to go around existing domestic guarantees and to spy on one’s own citizens through the back door. The dread that both legal and technological means designed with legitimate purposes such as counter-terrorism and crime prevention are also employed for total social control is now out there. In many aspects it looks like we are experiencing the end of privacy and opting for a ‘surveillance society’ instead. In the clutter of pressing issues, most of the recent scholarly attention has focused on the assessment and reform proposals of the existing, but as it turns out inadequate with respect to actual rights protection, domestic legal frameworks. This has left the obligations of the intruders under international human rights law unconsidered. Therefore, the present paper aims at evaluating the legality of such surveillance programs under the International Covenant on Civil and Political Rights and the European Convention on Human Rights.